Competitive Advantage Management Strategy and Corporate Survival Ability - Wildanika, Arifian; Atrhana, Nana; Saiful, Saiful; Chamariyah, Chamariyah (Institut Bisnis dan Informatika Kesatuan, 2024)
Companies begin strategic management by developing a clear vision and mission to guide the organization's strategy and ensure not only its survival but also its growth and competitive advantage. This process involves analyzing the internal and external environment, formulating strategies, implementing them, and evaluating and controlling them. In this study, an internal assessment was conducted using an internal advantage profile, followed by the development of an internal factor evaluation matrix. An external assessment using an environmental threats and opportunity profile was conducted, resulting in an external factor evaluation matrix. The analysis then proceeded to the matching stage, where the internal and external matrices were evaluated. A competitive profile was created through a survey, which incorporated key success factors into a competitive profile matrix. Finally, the positioning stage resulted in strategic recommendations using SWOT analysis and QSPM.